Dynamic data mining technique for rules extraction in a process of battery charging (vol 8, pg 1252, 2008) - Aliev, R. A.; Aliev, R. R.; Guirimov, B.; Uyar, K. (Elsevier Science Bv, 2008)
[Abstract Not Available]